Gender differentials and old age survival in the Nairobi slums, Kenya - Bennett, Rachel; Chepngeno-Langat, Gloria; Evandrou, Maria; Falkingham, Jane (Social Science & Medicine, 2016)
This paper examines gender differentials in survival amongst older people (50+ years) in the Nairobi slums and to the best of our knowledge is the first study of its kind in an urban African setting. The results provide evidence contrary to the expected paradox of poorer self-rated health yet better survival amongst older women. Older women in the Nairobi slums have poorer self-rated health and poorer circumstances across other factors, including disability and socio-economic status. Further, older women in the slums do not have better survival. The conventional female advantage in mortality only becomes apparent after accounting for the cumulative influence of individual characteristics, social networks, health and socio-economic status, suggesting the female advantage in unadjusted old-age mortality does not apply to contexts where women experience significant disadvantage across multiple life domains. This highlights the urgent need to redress the support, status and opportunities available for women across the life course in contexts such as the Nairobi slums. In addition, a greater number of factors differentiate mortality risk amongst men than amongst women, suggesting inequality amongst slum dwelling older men and highlighting the need for gender sensitive interventions which account for the particular needs of both genders in old age.
Keywords: 2000 à aujourd'hui; afrique; approches et analyses; bidonvilles; environnement; inégalités; kenya; personnes âgées; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; santé; sexisme; systèmes d'oppressions; thématiques

A gendered human rights analysis of Ebola and Zika: Locating gender in global health emergencies - Davies, Sara E.; Bennett, Belinda (International Affairs, 2016)
Globally gender remains a key factor in differing health outcomes for men and women. This article analyses the particular relevance of gender for debates about global health and the role for international human rights law in supporting improved health outcomes during public health emergencies. Looking specifically at the recent Ebola and Zika outbreaks, what we find particularly troubling in both cases is the paucity of engagement with human rights language and the diverse backgrounds of women in these locations of crisis, when women-specific advice was being issued. We find the lessons that should have been learnt from the Ebola experience have not been applied in the Zika outbreak and there remains a disconnect between the international public health advice being issued and the experience of pervasive structural gender inequalities among those experiencing the crises. In both cases we find that responses at the outbreak of the crisis presume that women have economic, social or regulatory options to exercise the autonomy contained in international advice. The problem in the case of both Ebola and Zika has been that leaving structural gender inequalities out of the crisis response has further compounded those inequalities. The article argues for a contextual human rights analysis that takes into account gender as a social and economic determinant of health.
Keywords: 2000 à aujourd'hui; 2010-2019; afrique; amérique latine; amériques; approches et analyses; care; droits des femmes*; inégalités; périodes historiques; ressource en ligne; régions géographiques; santé; santé publique; systèmes d'oppressions; thématiques

Les images des passions adolescentes: Des photographies d'expression faciale aux images scans dans la construction d'un cerveau adolescent émotionnel et sexué - Gumy, Christel (Revue d'anthropologie des connaissances, 2013)
Les recherches en neurosciences utilisant des sets de photographies d’expression faciale afin de tester, à l’aide des techniques d’imageries, les réactions émotionnelles des adolescent-e-s ont participé à établir un modèle neurobiologique de l’adolescence. Ce modèle, qui postule que la configuration cérébrale particulière à cette période de la vie soumet les jeunes personnes à un déficit de contrôle émotionnel, tend à s’imposer dans le domaine des sciences de l’adolescence, particulièrement en lien avec la question des prises de risque. Cet article propose d’investiguer le processus par lequel les neurosciences cognitives ont produit, à partir de portraits photographiques d’acteurs mimant des émotions, des stimuli valides qui permettent de rendre visible par le biais de l’IRMf une différence cérébrale discriminant d’une part 590 les adolescent-e-s et les adultes et d’autre part les jeunes filles et les jeunes garçons dans la gestion de l’information émotionnelle. En effet, le cerveau émotionnel adolescent est construit selon deux hiérarchies enchâssées : si la différence d’âge fait figure de hiérarchie fondatrice, celle de sexe constitue un élément tantôt moteur tantôt modérateur à l’intérieur de celle-ci.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; afrique; approches et analyses; cours; discipline; nouvelle-guinée; premier cycle; pédagogie; périodes historiques; recherche; régions géographiques; santé; sciences humaines; soc2051; sociologie; thématiques

Vieillissement réussi : perception des femmes aînées immigrantes de l’Afrique noire à Montréal - Noubicier, Agnès Florette; Charpentier, Michèle (Santé mentale au Québec, 2013)
Le présent article s’intéresse aux femmes aînées des communautés ethnoculturelles de l’Afrique noire. Il a pour but de présenter le sens qu’elles donnent au « vieillissement réussi » dans leur pays d’accueil, et de mettre en évidence les facteurs qu’elles considèrent comme essentiels pour expérimenter « un maximum de satisfaction et de bonheur » au cours de cette étape de leur vie. Il s’appuie sur une étude qualitative exploratoire menée auprès de sept femmes âgées de 65 à 77 ans qui ont immigré au Québec alors qu’elles avaient plus de 50 ans. L’étude met en relief des femmes aux identités multiples et aux vieillissements différentiels, pour qui le « vieillissement réussi » est tributaire de leur implication dans la famille et dans la société, de la foi et de l’autonomie financière. L’analyse des résultats sous un angle intersectionnel permet aussi de noter que les femmes aînées immigrantes de l’Afrique noire connaissent des difficultés en raison de l’entrecroisement des effets dus à leur âge, leur appartenance ethnique et leur genre, avec d’autres aspects liés à leur identité tels que la culture, la langue, le sexe, le parcours migratoire. Une multitude d’obstacles jonchent alors leur processus de vieillissement et influent sur leur conception du « vieillissement réussi
Keywords: 2000 à aujourd'hui; accomplissement; afrique; afrique noire; amériques; approches et analyses; cours; discipline; femmes aînées; femmes immigrantes; intersectionnalité; périodes historiques; québec; récits de vie; régions géographiques; santé; santé mentale; sciences humaines; soc1061; sociologie; thématiques; travail social; vieillissement

Femmes africaines séropositives en quête d’asile. Opportunités et contraintes de la politique migratoire canadienne - Cognet, Marguerite; Hoyez, Anne-Cécile; Poiret, Christian; Adam-Vézina, Émilie (Revue européenne des migrations internationales, 2012)
Cet article explore certains aspects des trajectoires d’exil de femmes réfugiées de la Région des Grands Lacs africains vers le Canada et atteintes du VIH-sida. Si les facteurs pré et post migratoires peuvent avoir un impact sur leurs conditions de vie et leur santé, l’angle que nous avons privilégié ici traite des effets des conditions législatives d’accès au territoire et aux soins pour ces migrantes. Après un bref exposé du contexte législatif canadien qui régit l’entrée sur le territoire et des dispositions relatives aux migrants malades et en particulier aux personnes séropositives au VIH nous montrerons, au travers des récits des femmes rencontrées, fuyant principalement des violences et persécutions genrées, comment ces politiques influencent leur trajectoire et leur santé. Nous verrons que la législation canadienne pose un ensemble de contraintes pour les réfugiées séropositives, tout en constituant une ressource mobilisable propre fournissant certaines opportunités.
Keywords: VIH; afrique; amériques; canada; cours; discipline; femmes immigrantes; politiques migratoires; ressource en ligne; réfugiées; régions géographiques; santé; sciences humaines; soc1061; sociologie; thématiques; violences; violences d'état; violences de genre; violences sexistes et sexuelles

Efficacy of micro-financing women's activities in Côte d'Ivoire: Evidence from rural areas and HIV/AIDS-affected women - Binaté Fofana, Namizata (Wageningen Academic Publishers, 2010)
This book deals with the effectiveness and the capability of microfinance institutions (MFIs) to enhance women's livelihoods and empowerment and to mitigate the effects of HIV and AIDS in Côte d'Ivoire. The results show that MFI credit causes positive and negative effects. MFI credit has improved incomes, the level of farm production and human and social capital. MFI credit has also enhanced women's decision-making power within households due to their new ability to contribute to the improvement of the household standard of living. Furthermore, women's empowerment regarding the demand for and the use of credit give them more opportunity to obtain MFI credit. Despite the positive effects of MFIs on women's income, this publication shows that loan repayment was not successful among some female borrowers due to the fact that the loan has not been used for investment purposes. For MFIs, the diversion of loans can endanger their functioning and sustainability and therefore their effectiveness in rural areas. Regarding HIV, this book highlights the diversity and the specificity of the way HIV-affected individuals are financially supported by credit institutions. Both the direct and indirect effects of HIV and AIDS on women's livelihood and MFIs are analysed.
Keywords: Infections transmisibles sexuellement et par le sang; OFDIG; VIH; afrique; côte d'ivoire; discipline; femmes*; finance; microfinance; régions géographiques; santé; sciences de la gestion; thématiques; économie